Oscillatory brain activity related to control mechanisms during laboratory-induced reactive aggression - Krämer, Ulrike M.; Münte, Thomas F.; Richter, Sylvia; Kopyciok, Robert P. (Frontiers in Behavioral Neuroscience, 2009)
Aggressive behavior is a common reaction in humans after an interpersonal provocation, but little is known about the underlying brain mechanisms. The present study analyzed oscillatory brain activity while participants were involved in an aggressive interaction to examine the neural processes subserving the associated decision and evaluation processes. Participants were selected from a larger sample because of their high scores in trait aggressiveness. We used a competitive reaction time task that induces aggressive behavior through provocation. Each trial is separated in a decision phase, during which the punishment for the opponent is set, and an outcome phase, during which the actual punishment is applied or received. We observed provocation-related differences during the decision phase in the theta band which differed depending on participants’ aggressive behavior: High provocation was associated with an increased frontal theta response in participants refraining from retaliation, but with reduced theta power in those who got back to the opponent. Moreover, more aggressive decisions after being punished were associated with a decrease of frontal theta power. Non-aggressive and aggressive participants differed also in their outcome-related response: Being punished led to an increased frontal theta power compared to win trials in the latter only, pointing to differences in evaluation processes associated with their different behavioral reactions. The data thus support previous evidence for a role of prefrontal areas in the control of reactive aggression and extend behavioral studies on associations between aggression or violence and impaired prefrontal functions.